Spesies Kumbang Kotoran (Coleoptera: Scarabaeidae) di Taman Nasional Gunung Palung Kalimantan Barat - Kustiati, Valeria Cacih Malina, Junardi (Jurnal Protobiont, 2018)
Dung beetles are invertebrates that an important ecosystem balance as decomposers. The distribution of beetles are influenced by the habitat form and the presence of animal feces. Gunung Palung National Park has an area 90,000 ha, in which there is Cabang Panti Research Station which a tropical forest with various types of habitats and animals. This research aims to determine the species of dung beetles in Cabang Panti Research Station. The research was located in six different habitats, such as peat swamp, freshwater swamp, kerangas, alluvial, lowland sandstone and lowland granite. Dung beetles were collected by baited pit-fall trap method plus feed of orangutan’s and human’s feces. Dung beetles found in Cabang Panti Research Station is 1939 individuals, 3 subfamilies, 7 tribes, 11 genus and 32 species. Three subfamilies were found consist of Aphodiinae (1 species), Coprinae (27 species) and Scarabaeinae (4 species). The most commonly found species of dung beetles from Onthophagus Genus (21 spesies). The most individuals of dung bettles are Paragymnopleurus maurus (1259 individuals). The highest number of species is found in the type of kerangas habitat (23 species) and the lowest is found in type of peat swamp habitat (15 species).